(i) Given
"\\frac {dy} {dt} = \\frac{(1+t^2)}{t}"
integrating both sides,
"\\int dy = \\int (\\frac{1+t^2}{t}) dt"
solving it, we obtain
"y = lnt + \\frac{1}{2}t^2 +C"
applying the condition, y(t=1) = 0
"c = -\\frac{1}{2}"
so equation will be,
"y = lnt + \\frac{1}{2}t^2 -\\frac{1}{2}"
Domain of y is "[0,\\infin)"
(ii) Given "(t+1)\\frac{dy}{dt} = 1-y"
integrating on both sides,
"\\int\\frac{dy}{1-y} = \\int\\frac{dt}{1+t}"
"-ln(1-t) = ln (1+t)+lnC"
applying the condition, y(t=0) = 3
"C = -\\frac{1}{2}"
so equation will be,
"y = 1 + \\frac{2}{1+t} = \\frac{t+3}{t+1}"
Domain for y is "\\R" - {1} where R is real number.
Comments
Leave a comment